Cognitive dissonance, pessimism, and behavioral spillover effects - David L. Dickinson; Robert J. Oxoby (Institute for the Study of Labor (IZA), 2007)
This paper reports results from a unique two-stage experiment designed to examine the spillover effects of optimism and pessimism. In stage 1, we induce optimism or pessimism onto subjects by randomly assigning a high or low piece rate for performing a cognitive task. We find that participants receiving the low piece rate are significantly more pessimistic with respect to performance on this task. In stage 2 individuals participate in an ultimatum game. We find that minimum acceptable offers are significantly lower for pessimistic subjects, though this pessimism was generated in a completely unrelated environment. These results highlight the existence of important spillover effects that can be behaviorally and economically important for example, pessimism regarding one's initial conditions (e.g., living in poverty) may have spillover effects on one's future labor market outcomes.
urn:nbn:de:101:1-2008032820
Keywords: 330; Verhaltensökonomik; Spillover-Effekt; Kognition; Verhandlungstheorie; Test